Variable transduction of thyroid hormone signaling in structures of the mouse brain - Richárd Sinkó; Federico Salas-Lucia; Petra Mohácsik; Emese Halmos; Gábor Wittmann; Péter Egri; Barbara M. L. C. Bocco; Alice Batistuzzo; Tatiana L. Fonseca; Csaba Fekete; Antonio C. Bianco; Balázs Gereben (Proceedings of the National Academy of Sciences, 2025)
L-thyroxine (L-T4) monotherapy is the standard treatment for hypothyroidism, administered daily to normalize TSH levels. Once absorbed, T4 is converted to T3 to alleviate most symptoms. However, this treatment abnormally elevates plasma T4 levels in over 50% of patients. Using L-T4-treated Thyroid Hormone (TH) Action Indicator mice, which express a T3-regulated luciferase (Luc) reporter, we examined whether these T4 elevations disrupt TH signaling. Hypothyroid mice exhibited reduced Luc expression across brain regions, and L-T4 treatment failed to restore T3 signaling uniformly. There was also variability in the activity of type 2 deiodinase (D2), the enzyme that generates most brain T3. Intracerebroventricular T4 administration achieved higher elevation of Luc expression in the mediobasal hypothalamus compared to the cortex, and studies on cultured cortical astrocytes and hypothalamic tanycytes revealed cell-type-specific responses to T4. In tanycytes, exposure to T4 sustained D2 activity, leading to progressive T3 signaling, whereas in astrocytes, T4 exposure triggered a drop in D2 activity, limiting T3 production through a ubiquitin-dependent, self-limiting mechanism. The sustained D2 activity in tanycytes was linked to rapid deubiquitination by USP33, as confirmed using a ubiquitin-specific protease (USP) pan-inhibitor and USP33 knockout mice. In conclusion, the brain’s response to L-T4 treatment is heterogeneous, influenced by cell-specific regulation of D2-mediated T3 production. While cortical astrocytes exhibit limited T3 signaling due to D2 ubiquitination, tanycytes coexpressing USP33 amplify T3 signaling by rescuing ubiquitinated D2 from proteasomal degradation. These findings provide mechanistic insights into the limitations of L-T4 therapy and highlight the need for tailored approaches to managing hypothyroidism.